Pengaruh Perputaran Modal Kerja dan Struktur Modal Terhadap Profitabilitas Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2019-2021 - Muhammad Anang Maulana; Nurwani Nurwani (Politeknik Ganesha Medan, 2022)
The survival of the company is influenced by various factors, one of which is profitability. There are several companies that experienced a decline in the profitability of companies listed on the Jakarta Islamic Index (JII) in the 2019-2021 period. This study aims to partially and simultaneously examine the effect of working capital turnover and capital structure on company profitability. The population in this study were 30 companies listed on the Jakarta Islamic Index (JII) Indonesia in the 2019-2021 period and a sample of 16 companies using purposive sampling technique. The data were processed using multiple linear regression analysis. The results of this study state that first, working capital turnover has a significant effect on profitability partially. Second, it states that the capital structure has no partial significant effect on profitability. Third, it states that working capital turnover and capital structure have a significant effect on profitability simultaneously.